Energy-saving potential for centrifugal pump storage operation using optimized control schemes - Hieninger, Thomas; Goppelt, Florian; Schmidt-Vollus, Ronald; Schlücker, Eberhard (Energy Efficiency, 2021)
In this paper, we present the energy-saving potential of using optimized control for centrifugal pump–driven water storages. For this purpose, a Simulink pump-pipe-storage model is used. The equations and transfer function for steady-state and transient system behavior are presented and verified. Two different control strategies—optimum constant flow rate and level guided speed control—are compared to an allegedly optimal-driven pump with constant rotational speed. Twelve centrifugal pumps between 1 and 120 kW nominal power are evaluated to analyze the influence of different system parameters. The system characteristics, which are the static head, dynamic head factor, and maximum filling head, are varied 25 times for each pump in consideration of the pump’s best efficiency point. Thus, 300 different systems are optimized for each control strategy and compared to the constant speed control. The results are analyzed and the relevant system’s parameters, which have the most significant impact on energy savings, are shown. This theoretical energy–saving potential is verified with measurements, which show the high impact of the part load losses of the frequency converter and the electric motor. A law for identifying and estimation potential energy savings is developed using this information. Four use cases are analyzed with this law. It is shown that for a cost-minimal operation, not only the savings potential but also the operating time is decisive.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Centrifugal pumps; Control optimization; Energy efficiency; Pump system modeling; Storage filling strategies